An understanding the determination of life insurance premium: Shariah compliant in the Islamic insurance concept and practice - Kusairi, Suhal; Saputra, Jumadil; Sanusi, Nur Azura (2015)
The main objective of the insurance is to uphold a sense of solidarities among the parties involved, shared responsibility on the basis of mutual cooperation in protecting the individual against unexpected risk.Insurance is one of tools to minimize or transfer risk which has existed for individuals to the insurance company against future loss faced by the policyholder or insured. The Islamic insurance based on the concept of Ta’awun that means mutual assistance to eliminate forbidden elements accordance with the teachings of Islam such as riba, gharar and maysir.The determination of life insurance premium, such as stated by (Bacinello, et al., 2009) that risk is extremely important and crucial role in life insurance policy.This paper aims to investigate the distinction of setting rates taking into account risk which applied by conventional and Islamic insurance (Takaful).This paper employs using the net single and Annual Level premium formula, the data analysis using numerical example.We found that between conventional and Takaful insurance systems utilize similar methods in the calculation of insurance premium whereas they consider the pure risks faced by participant or insured.It means that conventional and Islamic insurance utilizing historical data, such as mortality rate, expected return rate, expected costs and expected amount of claims.Even though both systems look like apply a similar approach, but the conventional insurance, it is calculated to mitigate or minimize risk of the insurance company against an amount of claim faced in the future as long as insurance enforced until the contract ends.In simple terms it can be called to avoid insolvency of the insurance company. Conversely, Takaful insurance intended to share fair value among participant in determining benevolence through tabarru fund.This means that every participant must pay a premium tabarru to support one another which contributed sufficient amount to cover unexpected claims among them and to uphold mutual fund as evidence the sense of mutual cooperation and brotherhood among participants